Shiga toxin-producing Escherichia coli outbreak in a childcare facility - Revercez, Audrey; Mahieu, Romain; Clément de Cléty, Stéphan; Rebuffat, Elisabeth; De Viron, Louise; Crombé, Florence; Piérard, Denis; Goetghebuer, Tessa (Belgian Journal of Paediatrics, 2023)
Haemolytic uremic syndrome (HUS) is typically associated with Shiga toxin-producing Escherichia coli (STEC). We describe two cases of HUS occurring in a childcare facility. We collaborated with the National Reference Centre for STEC to screen all 77 children and 27 adults present at the childcare facility. Shiga toxin Escherichia coli was detected in 7 children (9%) and 1 symptomatic sibling. Only one section was touched, 8 out of 29 children from the “big” section (28%) were affected. The high prevalence of Shiga toxin Escherichia coli carrying in childcare facilities supports the need for early hygiene measures and information to parents.